2013
DOI: 10.1111/tpj.12148
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of the Burkholderia glumae type III secretion system as an efficient tool for translocating pathogen effectors to monocot cells

Abstract: SUMMARYGenome sequences of plant fungal pathogens have enabled the identification of effectors that cooperatively modulate the cellular environment for successful fungal growth and suppress host defense. Identification and characterization of novel effector proteins are crucial for understanding pathogen virulence and host-plant defense mechanisms. Previous reports indicate that the Pseudomonas syringae pv. tomato DC3000 type III secretion system (T3SS) can be used to study how non-bacterial effectors manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Plant pathogenic fungi often overcome host immunity through the action of effector proteins 42 . To experimentally identify novel U. virens effectors, a pEDV-based screen was performed for 30 randomly selected putative effectors in which a type III secretion system of the emerging rice pathogen Burkholderia glumae was used to translocate these putative secreted proteins into plant cells to identify effectors that suppress hypersensitive responses (HR) in Nicotiana benthamiana 43 . The screen showed that 4 out of the 30 putative effectors such as UV_2964 had very strong HR suppressive ability, 4 including UV_5215 had a strong suppressive effect, 10 effectors had a weak effect, and others, for example, UV_6470 had little or no effect on inhibiting HR in N. benthamiana (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant pathogenic fungi often overcome host immunity through the action of effector proteins 42 . To experimentally identify novel U. virens effectors, a pEDV-based screen was performed for 30 randomly selected putative effectors in which a type III secretion system of the emerging rice pathogen Burkholderia glumae was used to translocate these putative secreted proteins into plant cells to identify effectors that suppress hypersensitive responses (HR) in Nicotiana benthamiana 43 . The screen showed that 4 out of the 30 putative effectors such as UV_2964 had very strong HR suppressive ability, 4 including UV_5215 had a strong suppressive effect, 10 effectors had a weak effect, and others, for example, UV_6470 had little or no effect on inhibiting HR in N. benthamiana (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR products were digested with the corresponding restriction emzymes and subcloned into pEDV 70 . Burkholderia glumae competent cells were prepared as described with minor modifications 43 . These pEDV constructs were transformed into B. glumae by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…Such broad activity of an NLR-triggered immune response has previously been reported in A. thaliana, but not yet in monocotyledonous plants. Indeed, the expression of the effectors ATR1 and ATR13 from the oomycete pathogen Hyaloperonospora parasitica fused to bacterial type-III secretion signals in P. syringae triggered resistance to this bacterial pathogen in A. thaliana accessions carrying the corresponding R genes RPP1 or RPP13 (Rentel et al, 2008;Sharma et al, 2013;Sohn et al, 2007). In addition, the introduction of ATR13 into turnip mosaic virus rendered the recombinant virus avirulent on A. thaliana accessions possessing RPP13 (Rentel et al, 2008).…”
Section: Recognition Of a Fungal Effector Triggers Resistance To Bactmentioning
confidence: 99%
“…The bacterial pathogen of rice, Burkholderia glumae, was used in a rice leaf sheath inoculation assay for in planta expression, and subcellular localization analyses of effector proteins of the rice blast fungus Magnaporthe oryzae (Sharma et al 2013). In the same study, the B. glumae system was shown to deliver fluorescently labelled fungal effectors to wheat and barley leaf sheath cells and, therefore, this system may be applied for effector discovery.…”
Section: Bacterial Type III Secretion System-based Expressionmentioning
confidence: 99%